Software Agent Negotiation Development: An Experience Report - Cheah, Wai Shiang; Kulathuramaiyer, Narayanan; Seng, Wai Lok (IEEE, 2006)
Negotiation involves the execution of rules and interaction among the agents toward the agreement, objective or outcomes. It is a complex process and need careful study and design. This paper focuses on experience sharing under the development of negotiation approach in a booking application (e.g. Smart LectureTheatre). It consists of the conceptual ideal of negotiation as well as the methodology for life cycle development. The development life cycle has been structured into five phases: locution determination, interaction protocol design, autonomy determination, agent binding and agent implementation. A simple negotiation application has been experimented for a simple argumentation negotiation application and an intelligent-based argumentation negotiation application. This paper has demonstrates the importance and capability of this methodology in structuring agent negotiation.